Data‐driven glass/ceramic science research: Insights from the glass and ceramic and data science/informatics communities. Issue 11 (30th July 2019) - De Guire, Eileen; Bartolo, Laura; Brindle, Ross; Devanathan, Ram; Dickey, Elizabeth C.; Fessler, Justin; French, Roger H.; Fotheringham, Ulrich; Harmer, Martin; Lara‐Curzio, Edgar; Lichtner, Sarah; Maillet, Emmanuel; et al.
Abstract: Data‐driven science and technology have helped achieve meaningful technological advancements in areas such as materials/drug discovery and health care, but efforts to apply high‐end data science algorithms to the areas of glass and ceramics are still limited. Many glass and ceramic researchers are interested in enhancing their work by using more data and data analytics to develop better functional materials more efficiently. Simultaneously, the data science community is looking for a way to access materials data resources to test and validate their advanced computational learning algorithms. To address this issue, The American Ceramic Society (ACerS) convened a Glass and Ceramic Data Science Workshop in February 2018, sponsored by the National Institute for Standards and Technology (NIST) Advanced Manufacturing Technologies (AMTech) program. The workshop brought together a select group of leaders in the data science, informatics, and glass and ceramics communities, ACerS, and Nexight Group to identify the greatest opportunities and mechanisms for facilitating increased collaboration and coordination between these communities. This article summarizes workshop discussions about the current challenges that limit interactions and collaboration between the glass and ceramic and data science communities, opportunities for a coordinated approach that leverages existing knowledge in both communities, and a clear path toward the enhanced use of data science technologies for functional glass and ceramic research and development.